General practice database on mortality in adults on methylphenidate: cohort study - Bruno Stricker; Katia Verhamme; Kiki Cheung (BMJ Open, 2022)
Objectives Methylphenidate is a ‘prescription only’ drug against attention disorders which is increasingly used by adults. We investigated whether methylphenidate in adults was associated with an increased risk of psychiatric events such as depression, and suicide attempt and overall mortality.Design A population-based matched cohort design.Setting The Integrated Primary Care Information system, a general practitioners (GP) database in the Netherlands with a source population of 2.5 million inhabitants.Participants During the study period between 1 June 1996 and 1 January 2018, 8905 adults started methylphenidate and were matched to 10 non-users on sex, age, GP practice and ad prescription date. The total study population consisted of 97 198 participants.Main outcome measures Serious psychiatric events such as depression and suicide attempts, and overall mortality.Analyses Risks of development of each event during the use of methylphenidate were expressed as HR with 95% CI, adjusted for relevant confounders with methylphenidate as a time-dependent determinant. Additional adjustment was performed for the intervention (‘intention-to-treat’).Results Although during follow-up, the unadjusted risks of depression and suicide attempt were strongly increased in users, depression and psychosis became non-significant after adjustment for alcohol-abuse and substance-abuse and psychiatric disease in the medical history and after adjustment for ‘intention-to-treat’. However, the risk of suicide attempts remained significantly increased after full adjustment (HR 2.0; 95% CI 1.1 to 3.6), and was highest in women and in participants within the age-group of 18–40 years. The unadjusted risk of overall mortality was strongly increased, but this lowered to a significant 30% risk increase (HR 1.3; 95% CI 1.1 to 1.6) after full adjustment.Conclusion There is an increased risk of suicide attempts in adults up to 40 years of age after starting methylphenidate and this risk should be carefully considered before prescribing to this group.